The protective effects of resveratrol, H2S and thermotherapy on the cell apoptosis induced by CdTe quantum dots. (June 2017) - Wu, Tianshu; Zhan, Qingling; Zhang, Ting; Ang, Shengjun; Ying, Jiali; He, Keyu; Zhang, Shihan; Xue, Yuying; Tang, Meng
Abstract: Quantum dots (QDs) could be used in the field of biology and medicine as excellent nano-scale fluorescent probes due to their unique optical properties, but the adverse effects of QDs are always the obstruction for its usage in living organisms. In this study, we observed that CdTe QDs exposure decreased the cell viability while increased the apoptosis rates in the L929 cells. Apart from QD-induced oxidative stress indicated by excessive ROS generation, three signal transductions, including Akt, p38 and JNK, played important roles on the regulation of cell apoptosis by CdTe QDs exposure as well. In order to reduce the toxicity of CdTe QDs, we explored the protective effects of three treatments, i.e. resveratrol, H2 S and thermotherapy at 43 °C, against the cell apoptosis elicited by CdTe QDs. The results showed that resveratrol, H2 S and thermotherapy at 43 °C were capable of attenuating cell apoptosis and intercellular ROS production through inhibiting signal pathways of Akt, p38 and JNK, respectively. As there is only limited number of exogenous treatments reported to diminish the toxicity of QDs, our findings will provide a novel insight for researchers who try to reduce or even eliminate the adverse health effects of QDs. Highlights: CdTe QDs exposure induced cell death, apoptosis and excessive ROS generation in the L929 cells. Pretreatment with resveratrol, H2 S and thermotherapy at 43 °C reduced QD-induced cell apoptotic rates. Resveratrol, H2 S and thermotherapy at 43 °C inhibited the QD-induced activation of three signal pathways.